PENGARUH PENGUNGKAPAN INFORMASI SEGMEN OPERASI TERHADAP KETEPATAN PERAMALAN LABA - Hendra; Nunung Nuryani (Jurnal Akuntansi, 2023)
When businesses are so diversified, investors and investment analysts want more information about the details behind consolidated financial statements. In particular, they want the income statement, statement of financial position, and cash flow information on the individual segments that compose the total income figure. However, the rampant manipulation of financial statements, including manipulation of information on segment disclosures with the motive of distorting the performance of one segment for the benefit of another segment, has influenced analysts and investors in predicting company performance. Therefore, this study aims to examine the effect of operating segment information disclosure on earnings forecasting. In addition, this study also examines important determinants that affect the quality of segment information disclosure. Using the purposive sampling method, a sample of 74 companies in financial institutions listed on the Indonesia Stock Exchange was obtained for the 2015-2020 period. The results of this study indicate that the disclosure of operating segment information (based on business lines, geography, and segment reconciliation) does not prove to affect the accuracy of earnings forecasts. The results of this study also indicate that leverage, audit quality, firm size, and profitability are influential factors that determine the quality of segment information disclosure.